Factors Associated with the Development of Cataracts (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Cataract is the most common cause of reversible blindness worldwide, which has been associated with various causative risk factors. Hence, we aim to study the factors that might play a role in cataractogenesis.Materials and methods. A total of 240 eyes of 240 subjects were included for the study, which consisted of 120 cases with a cataract and 120 matched controls, and in them various factors like blood pressure, body mass index (BMI), smoking, sun exposure, and serum cholesterol were studied.Results: A statistically significant difference between the two groups. Subjects who were smokers, had a longer exposure to sun, and had higher serum cholesterol level were found to be positively associated with development of cataract. No significant association between BMI and blood pressure was observed.Conclusion: Higher cholesterol levels, increased sun exposure, and smoking habit play a role in the development of cataract, and these are modifiable risk factors. Hence, control of these might help in delaying formation and progression of cataract.